USING THREE STEPS INTERVIEW TECHNIQUE TO IMPROVE THE SPEAKING SKILLS OF THE NON-ENGLISH DEPARTMENT STUDENTS - Zainuddin Zainuddin (Universitas Islam Negeri Maulana Malik Ibrahim Malang, 2018)
This study was intended to apply three steps interview technique as a teaching technique to solve the problems in the teaching and learning of speaking recount text. The problems were the students had difficulties to understand and respond conversation in English, having grammar difficulties, fluency and content problem and they also had low motivation. The researcher therefore decided to use three steps interview as a teaching technique as an effective solution to solve this problem. The finding of this study showed that implementaation the three steps interview as a teaching technique could help students to speak recount text much better than before when they were taught by using other speaking instruction. 18 out of 19 students passed the 70 as the standard score. In addition, in terms of students’ involvement in the speaking class activity, there was an increase from 81% in Cycle 1 to 87.5% in Cycle 2